Vaksin Strategy as Enjoyment Chemical Approach for Senior High School Students - Layta Dinira (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Desire to apply knowledge gained in school is the characteristic of high school students. These characteristic actually has been accommodated into 2013 curriculum. However, low interest of high school students to study chemistry was still found. Various learning methods have been developed to improve learning interest in the classroom. The effort to increase students' interest in chemistry can also be done outside the classroom. In this paper will be presented a theoretical study of joyful learning real world chemistry through VAKSIN strategy during school break. The strategy will be given in two ways, through science camps or excursion. Materials to be provided during the science camp are making green chemistry paint, exploration of cat litters, and simulations of waste water purification. Excursion can go into two places, the industry or university. VAKSIN strategy will have positive impact on students, teachers, industries, and universities. Keywords: high school students, joyful learning, real world chemistry, VAKSIN strategy